GAYA HIDUP MAHASISWA DI KELURAHAN WENANG SELATAN KECAMATAN WENANG KOTA MANADO PROVINSI SULAWESI UTARA (STUDI DI WARUNG KOPI VAN OMEN) - Sucitra, Imelda Diana; Tasik, Femmy C. M.; Kandowangko, Nicolaas (HOLISTIK, Journal Of Social and Culture, 2020)
Lifestyle itself is a characteristic of a modern world, or commonly called modernity. Patterns of life that are considered worrying are, consumptive lifestyles that leave productive lifestyles. Consumptive is usually used to refer to consumer behavior that utilizes a value of money greater than the value of its production for goods and services that are not a basic need. The rapid growth of coffee shops in the city of Manado apparently also influenced changes in the lifestyle of young people, especially students. There is a striking difference between Mahasiawa's current lifestyle and previous generations. Students in the city of Manado now prefer to visit coffee shops rather than going to the mall.Â  Coffee shops are considered to have a more comfortable atmosphere and better interior decoration so that it attracts the interest of visitors who incidentally come from among students who have the habit of gathering and spending time with their peers. This research is located in the coffee shop "Van Omen" located in the city of Manado.Â  Activities carried out by students spend time at the Van Ommen coffee shop where activities that show a very diverse student lifestyle are carried out at the venue. Students already consider that hanging culture is a habitual activity that is valuable to doKeywords: Lifestyle, college Students, Coffee Houses